Preparation of Polycarbonate-ZnO Nanocomposite Films: Surface Investigation after UV Irradiation - Babak Jaleh; Sara Hamzehi; Reza Sepahvand; Saeid Azizian; Mahtab Eslamipanah; Reza Golbedaghi; Alireza Meidanchi; Rui Fausto (Molecules, 2022)
Polycarbonate (PC)-ZnO films with different percentages of ZnO were prepared by a solution stirring technique and subjected to ultraviolet (UV; λ = 254 nm) irradiation. Structural parameters of the samples and the effects of UV irradiation on the surface properties of the PC and PC-ZnO nanocomposites were evaluated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), water contact angle (WCA) measurements, and a Vickers microhardness (HV) tester. The XRD patterns of the nanocomposite films were found to show an increase in crystallinity with the increasing ZnO nanoparticles percentage. The WCA was found to be reduced from 90° to 17° after 15 h of UV irradiation, which could be ascribed to the oxidation of the surface of the samples during the irradiation and exposure of the ZnO nanoparticles, a result that is also supported by the obtained XPS data. The microhardness value of the PC-ZnO films including 30 wt.% ZnO enhanced considerably after UV radiation, which can also be attributed to the exposition of the ZnO nanoparticles after photodegradation of the PC superficial layer of the nanocomposite films.